239 An Audit on The Consenting Process For Orthopaedic Surgery During The COVID Pandemic. (12th October 2021) - Manoharan, G; Edakalathur, J; Akhbari, P; Potter, R
Abstract: Aim: The Royal College of Surgeons have published guidelines on consenting for treatment of patients when COVID-19 is present in society. Patients should be made aware that attending hospital for elective surgical procedures exposes them to the risk of contracting COVID-19, despite the stringent health and hygiene measures employed by hospitals and their staff. Our aim is to investigate whether orthopaedic patients are being appropriately consented for surgery during the COVID pandemic. Method: A prospective audit of 100 consent forms was performed. The forms were examined to identify whether COVID-19 risk was documented as a potential risk of surgery. Data was also collected on consented grade, patient length of stay and any complications post-operatively. Results: 56% of consent forms reviewed did not contain the risk of COVID documented in them. 34% of forms that did not state COVID risk were completed by consultants, 18% by fellows and 48% were by registrars. 24% of these patients had an in-patient length of stay of 3 or more days. 6% patients were suspected of COVID post-operatively and tested. 0% patients contracted COVID in this cohort. Conclusions: The Royal College of Surgeons COVID-19 Toolkit states that the risk of contracting COVID while in hospital is 0.45%. All patients should be made aware of this risk prior to proceeding with surgery. Only 44% of patients in our hospital have had this risk discussed and documented. This compliance level has to be significantly improved.